2004
DOI: 10.1002/dmrr.425
|View full text |Cite
|
Sign up to set email alerts
|

Longer breastfeeding is an independent protective factor against development of type 1 diabetes mellitus in childhood

Abstract: Longer exclusive and total breastfeeding appears as an independent protective factor against type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
97
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(106 citation statements)
references
References 45 publications
3
97
0
4
Order By: Relevance
“…The remaining 29 articles [8-13, 15-19, 21, 28-44] contained information from 34 independent studies, as information from five centres was taken from one article [15] and information from two centres was taken from another [19]. An investigator from each of the 34 studies was invited to provide raw data (or estimates from pre-specified analyses), but one author [40] could not be contacted.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 29 articles [8-13, 15-19, 21, 28-44] contained information from 34 independent studies, as information from five centres was taken from one article [15] and information from two centres was taken from another [19]. An investigator from each of the 34 studies was invited to provide raw data (or estimates from pre-specified analyses), but one author [40] could not be contacted.…”
Section: Search Resultsmentioning
confidence: 99%
“…The findings of this research seem inconsistent, as some studies have concluded that high birthweight is associated with increased diabetes risk [8] or reduced diabetes risk [9], while others have shown no association with type 1 diabetes risk [10]. Interpretation of these findings is made more difficult because studies have reported associations using many different categorisations of birthweight [8,[11][12][13][14], with some [15,16] only reporting findings for the extremes of birthweight and others [17][18][19][20][21] not reporting their birthweight results in any detail, concentrating instead on other findings. This could lead to reporting bias if the decision to report birthweight findings was influenced by whether or not results were interesting or 'statistically significant'.…”
Section: Introductionmentioning
confidence: 98%
“…Dado que la lactancia materna de forma exclusiva hasta los seis meses y con una alimentación complementaria adecuada hasta los dos años y más, se ha constituido como una de las estrategias más efectivas en la prevención de enfermedades prevalentes de la infancia, como son la enfermedad diarreica aguda y la enfermedad respiratoria aguda, y además, como factor protector frente a la obesidad, y otros tantos beneficios ampliamente descritos en la literatura científica (1)(2)(3)(4)(5)(6)(7)25), este estudio brinda algunas herramientas esenciales para orientar y complementar las estrategias de promoción de la alimentación infantil adecuada en la población de mujeres adolescentes, las cuales sean adaptadas a las características propias de su edad con el fin de promover la lactancia materna que contribuya al mejoramiento de la salud en la primera infancia.…”
Section: Discussionunclassified
“…Está asociada con la disminución de la mortalidad de bebés prematuros y con la presencia de infecciones respiratorias, digestivas y otitis media, con la reducción del riesgo de enfermedades crónicas como alergias, obesidad, diabetes e hipertensión, y con el aumento del desempeño en pruebas de desarrollo intelectual y motor, en comparación con los niños que no son amamantados (1)(2)(3)(4)(5).…”
unclassified
“…Previous studies have shown that various perinatal and early life factors are associated with type 1 diabetes, such as maternal age, birthweight and breastfeeding [13][14][15]. As such factors may differ in children born by Caesarean section, the second aim was to adjust the pooled estimate of the association between Caesarean section and type 1 diabetes for the influence of these potential confounders.…”
Section: Introductionmentioning
confidence: 99%